AN ANALYSIS OF TRANSLATION TECHNIQUE USED IN THE MOVIE SUBTITLE ENTITLED “THE KING’S SPEECH” - Hosnol Wafa; Hani Nur Amalia (Program Studi Bahasa Inggris, Universitas Panca Marga, 2022)
This research purposed to find the types of politeness strategies and to know the dominant strategy that used by officers to customers in Unit Condong, PDAM Kabupaten Probolinggo. Unit Condong is a branch of PDAM Kabupaten Probolinggo which has a function to provide fresh water for society especially in Condong Village. This study uses the qualitative method to analyzing the data which indicate the politeness strategies used by officers to customers in Unit Condong, PDAM Kabupaten Probolinggo. Therefore, the instruments are used to obtain the data observation. The researcher used tape recorder to collect the data of officers and customers. After the data are collected, the following steps are done, those are: (1) Data reduction, (2) Data display, (3) Conclusion drawing/Verification. The result of this study shows that there are three types of politeness strategies used by officers to customers in Unit Condong, PDAM Kabupaten Probolinggo such 34 (42%) Bald on record, 19 (24%) Positive Politeness, and 28 (34%) Negative politeness. Then the dominant of politeness strategies that commonly used by officers to customers in Unit Condong, PDAM Kabupaten Probolinggo is Bald on Record Strategy.